1969
DOI: 10.1111/j.1651-2227.1969.tb04751.x
|View full text |Cite
|
Sign up to set email alerts
|

The Venous Plasma Free Amino Acid Levels of Mother and Child During Delivery. Iii.

Abstract: Summary The plasma aminograms of mother's and cord vein plasma during delivery were studied in selected cases from a lower socio‐economi‐cal group in West Pakistan with a high incidence of intrauterine growth retardation of the foetus. There was a highly significant increase in the levels of the non‐essential amino acids glycine and ornithine in the mother's plasma and of glycine and proline in cord plasma. The plasma glycine/valine quotient was significantly increased in maternal as well as in cord plasma. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1970
1970
1986
1986

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…However, it is necessary to mention that no significant change in amino acid concentration was observed when in some experiments a second sample o f venous mother blood was obtained at the moment o f delivery; (2) the fetal blood is cord blood, and although the samples were obtained before the delivery o f the placenta, some changes may have occurred in the amino acid concentrations, and (3) the placenta is term placenta and may have been submit ted to some anoxic conditions during delivery. In general, the obtained individual levels of amino acids are in agreement with those previously published (7,10,14,15,23). However, some exceptions exist.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, it is necessary to mention that no significant change in amino acid concentration was observed when in some experiments a second sample o f venous mother blood was obtained at the moment o f delivery; (2) the fetal blood is cord blood, and although the samples were obtained before the delivery o f the placenta, some changes may have occurred in the amino acid concentrations, and (3) the placenta is term placenta and may have been submit ted to some anoxic conditions during delivery. In general, the obtained individual levels of amino acids are in agreement with those previously published (7,10,14,15,23). However, some exceptions exist.…”
Section: Discussionsupporting
confidence: 81%
“…Although it has been reported that the amino acid concentrations in the feto-maternal system are modified in pregnancy complicated by toxemia (5,15), Lindblad and Zetterstrom (15) found that in those cases in which normal infants were born, the only apparent modification was an increase o f the urea level in the cord plasma with no modification o f the amino acid concentrations. Since the increase o f the cord blood urea level appears to be secondary to an increase in the maternal plasma level of this metabolite and since in our group of hyper tensive mothers no increase of blood urea was present, it is possible that the results presented herein, although obtained in a group of pathologic pregnancies, may be completely explained by the mechanisms observed in the normal ones.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that placental insuffi ciency could be one of the determining factors o f this increase [10]. However in hypodystrophic newborns a rise in protidic catabolism as a consequence of diminished carbohydrate and fat stores [3,12,13] and a diminished supply of essential amino acids from the mother to the foetus [4] could be shown.…”
mentioning
confidence: 99%
“…In Figure 1, the plasma aminogram of a low birth weight infant receiving 3 g/kg, body wt, of FreAmine is compared with values for cord blood. The base line for cord blood is provided by our earlier work [12], as well as by the findings of Scandinavian investigators [23]. The point at issue is not the remarkable agreement between work conducted on the two sides of the Atlantic, but the striking deviation from normal brought about by an amino acid mixture based on the proportions of egg protein (FreAmine).…”
Section: Irrational Compositionmentioning
confidence: 99%